Bilateral Martin-Gruber and Marinacci Anastomoses in the Same Patient: A Case Report. (2nd July 2020) - Nimma, Anitha; Bhat, Sushanth
ABSTRACT: Anomalous innervations are commonly encountered on electrodiagnostic testing and may be mistaken for a pathological process, especially if seen in multiple nerves. While crossover of median-to-ulnar fibers in the forearm (Martin-Gruber anastomosis) has been frequently described, the corresponding ulnar-to-median crossover (Marinacci anastomosis) is much less commonly seen. There have been no reported cases of both of these anomalous innervations occurring together. We describe a novel case of bilateral Martin-Gruber and Marinacci anastomoses in the same patient. The importance of the case lies in the fact that the multiple pseudo-conduction blocks that result from these crossovers could potentially be misinterpreted as being pathological in nature, illustrating the need for electromyographers to be familiar with common anomalous innervations in the upper extremity and with techniques to identify them.